Credibility, Parasocial Interaction, and Informative Value: The Role of Trust in Stakeholders’ Decision Intention - Roro Ayu Rahmadhani; Rizky Fauzan; Erna Listiana; Nur Afifah; Ahmadi (Al-Qalam Institue, 2026)
The rapid growth of influencer marketing in Indonesia, particularly through social media platforms, has heightened the importance of influencer authenticity in shaping audience perceptions and decision-making. However, empirical studies examining the effectiveness of influencers who promote their own brands remain limited. This study aims to analyze the influence of credibility, parasocial interaction, and informative value on stakeholders’ decision intention, with trust serving as a mediating variable, within the context of educational brand management. Using a quantitative approach, data were collected through a questionnaire administered to 217 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The findings reveal that parasocial interaction has a positive and significant direct effect on decision intention, while credibility, parasocial interaction, and informative value significantly influence trust. In contrast, credibility and informative value do not show a significant direct effect on decision intention. Furthermore, trust is found to significantly mediate the relationships between credibility, parasocial interaction, and informative value and stakeholders’ decision intention. These results imply that effective educational brand management in the digital era should prioritize trust-building strategies by enhancing authentic communication, meaningful engagement, and the quality of information delivered to stakeholders in order to strengthen decision-making outcomes.